Bivariate Spectral Analysis of the Capital Asset Pricing Model - Goldberg, Michael A.; Vora, Ashok (Journal of Financial and Quantitative Analysis, 1978)
Ever since Markowitz introduced the concept of portfolio theory in 1952, one of the questions predominant in the minds of financial theorists has been the constituency of the investor's optimal asset portfolio. Research into this area, which became known as capital market theory, attempted to analyze the equilibrium relationships between assets. One of the products of this research was the widely accepted Capital Asset Pricing Model (CAPM) of Sharpe and Lintner.